Public trust in advisory mini-publics: the impact of recommendations and institutional design features - Himmelroos, Staffan; Jäske, Maija; Setälä, Maija (Informa UK Limited, 2026)
Deliberative mini-publics are among the most studied forms of citizen participation with an active global developer network. Mini-publics have shaped legislation and provided useful information for voters in many countries, but our knowledge on the public perceptions of these mechanisms remains ambiguous. The public generally trusts mini-publics, but often on different grounds than democratic theory expects. We ran a population-based survey experiment (n = 2992) in Finland to examine how information regarding the design features of an advisory mini-public - organizer, composition and competence - and its policy recommendations affect the wider public's trust in the mini-public. Our experiment is based on a real mini-public, Citizens' Jury on Climate Actions organized in 2021, with a mandate from the Ministry of the Environment. We find that reading about mini-public recommendations and their justifications increases overall trust in the mini-public. However, the design features of the mini-public process had no effect on these general trust judgements.